Automatic generation of Bond Graph models of process plants - Beez,S; Fay,A; Thornhill,NF (IEEE, 2008)
This paper presents an application for the automatic generation of Bond Graph models. The basis for this automated creation is a modified plant model in the XML-format according to the IEC PAS 62424 (CAEX). The application developed in the programming language C, extracts and converts the information which is, then, stored in a model file meeting the requirements and structure of the modelling/simulation-language Dymola. Bond Graphs are used as the modelling technique since they do not distinguish between different energy domains and, therefore, combine several advantages against other modelling techniques. The developed application can be used for multiple purposes such as simulations, visualizations and other specific tasks that might emerge during the planning and operation process of plants and other engineering systems. © 2008 IEEE.